Evolución del periodismo deportivo en medios digitales - Sancán Chiquito, Erick Santiago (2024)
Sports journalism is one of the most sought-after branches of communication today. Worldwide, there are millions of people who consume this type of content and the vast majority of them do so from some portal or website. Journalism as such appeared hundreds of years ago and its main objective was to inform society about something. At first it was done through pamphlets, which after a few years became printed newspapers. With the arrival of the Industrial Revolution, this process was speeded up: more sheets could now be printed in less time. Therefore, more information was disseminated than ever........